VIGNA RADIATA (MUNG BEANS) AS AN ALTERNATIVE CULTURE MEDIUM FOR TRYPTICASE SOY AGAR - Condrillon, Choren; Masong, Lovelyn; Sandoval, Chrystle Elyssa; Siojo, Chloe; Bustamante, Jeson (Asian Journal Of Medical Technology, 2024)
High costs of commercial culture media poses challenge in microbiology research, driving a quest for cost-effective culture mediums. The study investigates the potential of Mung beans (Vigna radiata) as a potential alternative culture medium for Trypticase Soy Agar (TSA). This study utilized a quantitative experimental research design with the use of Absolute Growth Index (AGI) Scale and Centers for Disease Control and Prevention (CDC) categorized characteristics of colony morphologies. Mung beans are ground into powder, mixed with 1.5% agar, and processed similarly to TSA. Four-quadrant streaking is performed, followed by incubation at 37°C for 24 hours. Test microorganisms include Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Candida albicans. Colony growth from both the formulated Mung Bean Agar (MBA) and TSA were scored according to AGI and compared with the use of two-way ANOVA. Colony morphology observations reveal that Mung Bean Agar (MBA) produces pinpoint, smooth, grayish, opaque, punctiform colonies with entire margins, whereas TSA yields small/medium, yellow, mucoid, transparent, circular colonies with entire margins. Statistical analysis shows no significant difference in AGI between MBA and TSA. In conclusion, MBA can serve as a cost-effective alternative to TSA for microbiological culture, offering a similar growth performance while being more economically feasible.